Po poti modre frankinje: Modra frankinja kot osnova vinskega turizma v Sevnici - Potočnik Topler, Jasna; Lisec, Andrej (2019)
On the Route of the Blaufränkisch: The Blaufränkisch as the Basis of Wine Tourism in Sevnica. Today, many destinations see their opportunities in wine tourism. New products are created, new partnerships made, and new experiences marketed. Within the framework of the Student Innovation Project for Social Benefit (ŠIPK) 2016-2020, a group of students from various faculties within the University of Maribor, in collaboration of the Institute of Culture, Sport, Tourism and Youth Affairs Sevnica, began preparations for the new wine route, putting forward the newly established autochthonous Slovenian variety, the Blaufränkisch. The winemakers, restaurants and accommodation establishments, local cultural and natural sights and other attractions of Sevnica are joined under the same name - "Blue Wine Route.” It is a name which bares two meanings in the Slovene language. Literally, it means the blue colour representing the blue skin of Blaufränkisch grapes. On the other hand, however, “modro” represents wisdom and responsibility. This monograph presents Sevnica, its history and characteristics. The tourist offer of the area is defined and a more detailed presentation of wine tourism offered. A new wine route has been formed, connecting local wine producers of Blaufränkisch as well as inns and restaurants that use it. Their close cooperation is crucial for the recognition of Sevnica by the Blaufränkisch variety.
Keywords: wine tourism; wine route; wine; Blaufränkisch; Sevnic